Juglans regia L. fruit pellicle extract-based bioreduction of silver nanoparticles: Structural features and in vivo therapeutic effects against ethanol-induced peptic ulcers - Afaf Al-Nadaf; Areej Awadallah; Rasha Hussein (GarVal Editorial Ltda., 2024)
Context: Peptic ulcers are a challenging problem. Silver nanoparticles (AgNPs) play a substantial role in bioactivity and have distinct characteristics. There are several biomedical uses for bioreduction nanotechnology. Historically, traditional healthcare has employed Juglans regia L. Aims: To evaluate how well fruit pellicle extract-derived bio-reduced silver nanoparticles (AgNP/FP) can treat peptic ulcers. Methods: Ultraviolet spectra, dynamic light scattering, transmittance electron microscopy, and Fourier transform infrared were used to characterize AgNPs and AgNP/FP. AgNPs and extracts were compared to omeprazole in ethanol-induced stomach ulcers in mice. Six groups of 36 mice were created at random. AgNPs were given orally to the experimental groups, using 300 mg/kg as a dose. The reference proton pump inhibitor, omeprazole, was employed as a control. Results: As evidenced by a falling ulcer index and an increase in the percentage of ulcer inhibition, bio-reduced AgNPs decreased the adverse effect of ethanol-induced stomach injury. Reduced mucosal damage and hemorrhagic lesions, necrobiotic alterations in the stomach epithelium, submucosal edema, and blood vessel congestion were all indicators of substantially reduced ethanol-induced gastric lesions and greater anti-inflammatory results. Conclusions: Fruit pellicle extract-derived bio-reduced silver nanoparticles have an efficacy similar to proton pump inhibitors like omeprazole and a lower incidence of possible side effects, making them a safe herbal therapy for ulcers.